MODERN APPROACHES TO MORTGAGE LENDING IN FOREIGN ECONOMIC PRACTICE - R. Khusikhanov (Вестник университета)
In the article the comparative characteristic of models of mortgage lending in the developed countries is carried out. Advantages and shortcomings of these models are marked out. The features of mortgage institutes created as a result of the international practice of mortgage lending are estimated.